Contratos náuticos y estructura fractal de las normas jurídicas (fletamento vs. transporte marítimo de mercancías: del contrato, a la institución) - Garcia Pita, José Luis (Revista de Derecho, 2019)
The classic question referring the limits between the different tipes of maritime contracts, and -concretely- between Freightments and Contracts of Carriage of Goods by Sea frequently suffers or is submitted to sudden turns and twists, during the process of spanish Maritime Law Reform. The Proposal of a new General Act, proposed by Socialists parliamentary Group, which is -“ad pedem litterae”- the same that the older 2008/ Project, defines the “Freightment Contract” [Contrato de Fletamento] in terms of full and absolute identification or equalization with the Contrac of Carriage of Goods by Sea, with the self-evident purpose of making the Owner -which is called “Carrier”- liable for thecarriage and custody of the goods on board, and thus erasing completely the older figure of the “Contrato de Fletamento” [Freightment], as a contract for the furniture of navigation services, for others´ account and under other’s instructions. It is done, this way, a “tabula rasa” of contractual Shipowner’s will, substituing his consent in obligating to carry and custody the goods by some kind of “receptum” or “involuntary bailment”, with deep roots in English Law, that distorts the nature of Freightment and Transport [or Carriage], as contracts, fruit of the private will and of his legitimate auto-normative power